6
$\begingroup$

I am proving $(x^n)'=nx^{n-1}$ by the definition of the derivative:

\begin{align} (x^n)'&=\lim_{h \to 0} {(x+h)^n-x^n\over h}\\ &=\lim_{h \to 0} {x^n+nx^{n-1}h+{n(n-1)\over 2}x^{n-2}h^2+\cdots+h^n-x^n\over h} \\ &=\lim_{h \to 0} \left[ nx^{n-1}+{n(n-1)\over 2}x^{n-2}h+\cdots+h^{n-1} \right] \end{align}

Because polynomial is continuous for every $x$, we can conclude that $\lim_{x_0\to 0}(x_0)^n=0$. Therefore $$\lim_{h \to 0} \left[ nx^{n-1}+{n(n-1)\over 2}x^{n-2}h+\dots+h^{n-1} \right]= nx^{n-1}$$

Is this proof valid?

$\endgroup$
  • 2
    $\begingroup$ this looks entirely correct $\endgroup$ – ncmathsadist Jun 22 '15 at 21:39
  • 4
    $\begingroup$ Well, unless $n$ is not an integer... but it seems you're set for the simple version. $\endgroup$ – MichaelChirico Jun 22 '15 at 21:40
  • $\begingroup$ The proof you give is correct only when $n$ is a positive integer. it is easy to extend the proof for negative integer $n$ as well. There are slight complications when proving the formula for rational $n$. The derivative formula amounts to the following standard limit $$\lim_{x \to a}\frac{x^{n} - a^{n}}{x - a} = na^{n - 1}$$ which I have proved in my post paramanands.blogspot.com/2013/11/… (see "Proof of Standard Limits"). $\endgroup$ – Paramanand Singh Jun 23 '15 at 4:03
9
$\begingroup$

It is correct, but too many ellipses tend to obscure a bit the proof. And ellipses are not very rigurous, if you ask me.

I'd rewrite it using this:

For $n\ge 2$ there exists some polynomial $P(x,h)$ such that $$(x+h)^n=x^n+nhx^{n-1}+h^2P(x,h)$$

$\endgroup$
  • 3
    $\begingroup$ Is rigor or understanding more important? $\endgroup$ – JacksonFitzsimmons Jul 3 '15 at 2:15
3
$\begingroup$

The proof in OP is correct if $n$ is a positive integer. For a generic real exponent $a$ we can start from the derivative of the exponential function $y=e^x \rightarrow y'=e^x$.

From the inverse function differentiation rule we find $y=\log x \rightarrow y'=\dfrac{1}{x}$ and (using the chain rule):

$$ y=x^a =e^{a \log x} \rightarrow y'=e^{a \log x} (a\log x)'=e^{a \log x} \dfrac{a}{x}=ax^{a-1} $$

$\endgroup$
  • $\begingroup$ I think you skipped the part when $n$ is rational. When $n$ is rational the derivative of $x^{n}$ can and should be calculated via algebraical means rather than using the theory of exponential and logarithmic functions. $\endgroup$ – Paramanand Singh Jun 23 '15 at 3:59
  • 1
    $\begingroup$ @Paramanand: This proof is valid for any $a \in \mathbb{R}$, so also rational. We can give a proof for rational exponents ( positive or negative) without use of the exponential function, but it is more laborious. Note that the derivative of the exponential function can be found very quickly by the definition of derivative using the fact that $e^{x+h}=e^xe^h$. $\endgroup$ – Emilio Novati Jun 23 '15 at 7:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.